IMPLEMENTATION OF ENTREPRENEURSHIP EDUCATION IN THE FAMILY ENVIRONMENT (PHENOMENOLOGY STUDY OF OYSTER MUSHROOM INDUSTRY CENTERS IN SEMPU DISTRICT, BANYUWANGI REGENCY) - Rizatul Khulaifa; F. Danardana MurwaniMurwani; Aniek Indrawati (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
To realize the entrepreneurial mindset, entrepreneurship education is needed to produce reliable and qualified entrepreneurs, where the family is the closest person who can provide such education. This study aims to determine how the process of entrepreneurship education in the family, knowing the cultivation of entrepreneurial spirit in children in the family, as well as knowing the constraints and obstacles to the process of entrepreneurship education in the family at the oyster mushroom industry centers Sempu District, West Java. The type of research used to achieve this goal is a type of qualitative research with phenomenological methods. The results showed that the application of entrepreneurial values in some families has been carried out, as seen by some children who participated in helping their parents ' businesses. The conclusion of this research is the application of entrepreneurial values in some family's oyster mushroom centers in the district Sempu has been implemented, but although the application of entrepreneurial values in the family in this community has been implemented, the understanding of entrepreneurship education and entrepreneurial values have not been fully understood